Application value of contrast‐enhanced ultrasonography in the treatment of uterine fibroids by high‐intensity focused ultrasound ablation: A retrospective study. Issue 1 (30th August 2022) - Zhang, Miao; Yin, Chengkun; Jiang, Jing; Chen, Yan; Wang, Juan; Wang, Qi; Zeng, Yuhua; Zhou, Honggui
Abstract: Purpose: To determine efficacy and safety of contrast‐enhanced ultrasonography (CEUS) in high‐intensity focused ultrasound (HIFU) ablation of uterine fibroids (UFs). Methods: We retrospectively reviewed women undergoing HIFU ablation for UFs between June 2018 and January 2020. Before and after HIFU, patients underwent CEUS and magnetic resonance imaging (MRI) examinations. The relationship between CEUS features and ablation rate was analyzed. The time–intensity curves on CEUS were measured before and after HIFU ablation, and compared with those obtained using MRI. Adverse reactions were recorded. Results: A total of 64 patients were included. The immediate HIFU ablation rate significantly differed between low‐, iso‐, and high‐enhancement UFs (87.2% ± 1.6%, 83.3% ± 2.1%, and 72.9% ± 3.1%, respectively; p  < 0.05). On CEUS, the peak time of the time–intensity curve was significantly longer after treatment than before treatment (32.2 ± 9.7 and 26.7 ± 9.4 s, respectively; p  < 0.05). Peak intensity was significantly lower after treatment than before treatment (13.7 ± 7.5 and 30.9 ± 11.2 dB, respectively; p  < 0.05). All measurements were comparable between CEUS and MRI. The most common peri‐ and post‐procedure adverse reaction was pain, which was temporary. Conclusion: CEUS could dynamically and safely evaluate the immediate effects of the HIFU ablation of UFs. Abstract : CEUS performs well in predicting the immediate effect of the HIFU ablation of UFs. CEUS is useful in necrosis and blood perfusion evaluation post HIFU ablation. CEUS is a cost‐effective way to evaluate immediate effect post UF HIFU ablation.